THE APPLICATION OF CONTEXTUAL TEACHING AND LEARNING (CTL) IN TEACHING AND LEARNING READING FOR THE ELEVENTH GRADE STUDENTS OF SMA N 1 JATINOM - Septi Yuliana; Ana Setyandari; Sri Haryanti (Widya Wacana: Jurnal Ilmiah, 2024)
The study aims to answer the question which becomes a problem of this study: “How is the application of the Contextual Teaching and Learning (CTL) in teaching and learning reading for the eleventh grade students of SMA N 1 Jatinom?”. The data are collected through observation, interview, and documentation in the process of the implementation of the Contextual Teaching and Learning (CTL) learning method. This study uses four steps to analyze data, namely data collection, data reduction, data display, and conclusions drawing. The step of application of Contextual Teaching and Learning (CTL) In the first step the teacher conveys the material to students and asks to listen to the material being explained. Secondly, the teacher asks students to read some of the material that has been explained. Thirdly, the teacher makes group discussions by dividing students into four groups, each group consisting of eight students. The fourth, students conducted discussions with their groups. Finally, students show the results of their discussion. After applying the Contextual Teaching and Learning (CTL) model, it becomes easier for students to understand the material and the teaching and learning process becomes more active and interactive. Keywords: application; reading; Contextual Teaching and Learning (CTL) model